(3efMI GdSdhc aj TQM JMaI Gdedhcs - (3HOQ GdOjf CHh eMeO eMehO Hf CMeO GdYjfis; (3GdQGRj , Rjf GdOjf eMeO Hf TeS GdOjf CHj HcQ Hf YHO GdbGOQ GdMfaj GdQGRj,J (B666 (3g` s ((3QeVGf Hf ehSi GdYWjai s)
(3ChdgG (B:s
(3Ef CMQi eG jedi ai JHGTjQ GdNWH CeG HYO aEf GdYHO GdabjQ Edi QHg GdZfi CHG eMeO GdYjfi GdMfai jbhd deG hbYJ ai GdOjGQ GdeUQjI QCjJ GdJQc ecHjf Ydi GdeNJUQ GdehShe HJMaI Gdedhc CQOJ Cf COhf dg TQMkG s
(3BNQgG (B:s
(3GfJgi cJGH GdUhe hjJdhg cJGH GdML s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3Gdabg GdESdGejs